The Affecting Factors of Compliance Diabetes Mellitus Type 2 Treatment in Pandemic Era - Febrinasari, Ratih Puspita; Solikah, Tri Agusti; Nasirochmi, Dyonisa; Dilma’aarij, Dilma’aarij (KEMAS: Jurnal Kesehatan Masyarakat, 2022)
Diabetes mellitus (DM) is one of the non-communicable diseases that cause serious health problems. This chronic disease requires lifelong treatment to prevent complications and death. In the pandemic era, DM became comorbid that contributed to the death rate in Covid-19 cases, so that patients with type 2 DM become important to comply with the treatment underway. Aim: This study aimed to evaluate the treatment compliance in patients with DM type 2 at the Purwodiningratan primary health care, Surakarta. Method: This study was conducted in 2020 used an analytical method with crosssectional design. Populations were all of the patients who experience DM type 2, sampling techniques used total sampling with 108 respondents. Univariate, bivariate analysis, and logistic regression were used in this study. Compliance levels measured used the MMAS-8 questionnaire. Result:  The results of this study were obtained from several independent variables that related to compliance with DM type 2 treatment. The descriptive analysis result of patient compliance showed that 70.4% of patients were obedient. The significant variable was the side effects on DM drugs with (OR = -0.44; 95% CI = -0.74 - 0.15; p = 0.003). Conclusion: Most of the patients were adherent to the treatment and the most influencing factor was the side effect of the drug.